2004
DOI: 10.1029/2003jb002689
|View full text |Cite
|
Sign up to set email alerts
|

Deep seismic imaging of the eastern Nankai trough, Japan, from multifold ocean bottom seismometer data by combined travel time tomography and prestack depth migration

Abstract: [1] The easternmost segment of the Nankai trough remained unruptured during the 1944 and 1946 earthquakes that affected the rest of the trench. It is therefore a zone of seismic gap that also undergoes a peculiar tectonic regime due to its proximity with the Izu collision zone. We investigate this area with densely sampled active seismic data. One hundred ocean bottom seismometers, spaced only 1 km apart, were deployed along a line perpendicular to the trough. A two-step tomographic approach, designed for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 77 publications
2
67
0
Order By: Relevance
“…The lower part of the Shikoku Basin displays a complex geometry influenced by basement topography (Ike et al, 2008b). Basement highs are also imaged within the subduction zone (Kodaira et al, 2003;Dessa et al, 2004), where they influence margin structure (Lallemand et al, 1992;Le Pichon et al, 1996;Park et al, 1999;Mazzotti et al, 2002;Bangs et al, 2006;Moore et al, 2009) and seismicity (Kodaira et al, 2000a;Park et al, 2004). The NanTroSEIZE expeditions focused on the Kumano transect, while earlier Ocean Drilling Program (ODP) and Deep Sea Drilling Project (DSDP) sites were drilled on the Muroto transect and the Ashizuri transects, respectively, in the central and western part of Shikoku Basin ( Fig.…”
Section: Geologic Setting and Previous Workmentioning
confidence: 99%
“…The lower part of the Shikoku Basin displays a complex geometry influenced by basement topography (Ike et al, 2008b). Basement highs are also imaged within the subduction zone (Kodaira et al, 2003;Dessa et al, 2004), where they influence margin structure (Lallemand et al, 1992;Le Pichon et al, 1996;Park et al, 1999;Mazzotti et al, 2002;Bangs et al, 2006;Moore et al, 2009) and seismicity (Kodaira et al, 2000a;Park et al, 2004). The NanTroSEIZE expeditions focused on the Kumano transect, while earlier Ocean Drilling Program (ODP) and Deep Sea Drilling Project (DSDP) sites were drilled on the Muroto transect and the Ashizuri transects, respectively, in the central and western part of Shikoku Basin ( Fig.…”
Section: Geologic Setting and Previous Workmentioning
confidence: 99%
“…smoothing operator), δs is the slowness update, and y is a temporary vector. The adjoint of the Jacobian matrix J † smears the traveltime residuals along the raypaths computed using the traveltime tables (Dessa et al, 2004). This back-projection approach is preferred to the back projection using the adjoint-state method (Sei and Symes, 1994;Leung and Qian, 2006;Taillandier et al, 2009), due to the small number of rays, which is faster to trace.…”
Section: Tomographymentioning
confidence: 99%
“…Traveltime inversion is the traditional method for generating accurate starting models (Bording et al, 1987;Dessa et al, 2004;Woodward et al, 2008;Prieux et al, 2013), whereas firstbreak picking is the first step toward shallow tomographic inversion (Zhu et al, 1992;Zelt and Barton, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Our imaged south ridge is the eastern most member of this ridge. Dessa et al (2004) also imaged a subducted ridge immediately west of the south ridge using high resolution OBS data. Park et al (2003) concluded from mapping that the western half of the ridge, which is located off the Kumano basin, is colliding with the back stop.…”
Section: Checkerboard Testmentioning
confidence: 99%